Selection of dental ceramics in an esthetic área: a case report - Germán Martínez-Galeano; Luisa Fernanda Pacheco-Muñoz; Lida Constanza López-Palomar (Universidad de Antioquia, 2017)
The use of full ceramic systems to restore teeth in the anterior area is today the preferred method over conventional metal-ceramic systems due to the combination of aesthetic and mechanical properties, in addition to the biocompatibility of these materials and the possibility they offer to minimize tooth preparation. However, due to the sensitivity of the technique while using these systems, especially those that require adhesive cementation, it is highly important to be familiar with their characteristics and indications in order to make the right choice according to each patient's conditions. The literature reports that the possible clinical failures of these materials are multifactorial, with occlusal instability being one of the causes. Therefore, their biomechanical behavior and the strict implementation of clinical protocols are necessary for successful long-term restorations. This article discusses the various adhesive restorative options to rehabilitate the anterior area and presents their application to a patient's clinical case with esthetic purposes.